Ternary liquid–liquid equilibrium data for n-Hexane-Benzene-DES (choline chloride/ethylene glycol, choline chloride/glycerol, choline chloride/urea) at 303 K and 101.3 kPa - Mohammed Awwalu Usman (Applied Petrochemical Research, 2020)
Abstract In this study, deep eutectic solvents (DESs) were prepared using choline chloride as hydrogen bond acceptor (HBA) and ethylene glycol (EG) or glycerol (GLY) or urea (U) as hydrogen bond donor (HBD) and were evaluated as solvents in the extraction of benzene from n-hexane. Six of such solvents were prepared using different molar ratios of HBA: HBD and code named DES1, DES2, DES3, DES4, DES5 and DES6. Liquid–liquid equilibria (LLE) data for the ternary systems of n-hexane-benzene-DESs were measured at 303 K and 101.3 kPa. Solubility data and mutual solubilities between n-hexane and DES were measured using the traditional cloud point method. The tie lines were obtained using titration and refractive index measurements on both phases (n-hexane phase and DES-phases). The ternary systems exhibit type-1 phase behavior. The Othmer-Tobias and Hands equations were applied to examine the reliability of the LLE data. The tie-line data were correlated using the nonrandom two-liquid (NRTL) and universal quasichemical (UNIQUAC) thermodynamic models, and their corresponding binary interaction parameters were determined. The results show that the maximum separation factors were 31.24, 462.00, 15.24, 37.83, 174.60 and 126.00 for DES1, DES2, DES3, DES4, DES5 and DES6, respectively. The glycerol based DES (DES2 and DES5) show the highest separation factors and thus considered the most suitable for separating benzene from hexane. The regression coefficient for both Othmer-Tobias and Hand equations are higher than 0.99 for all DESs, indicating the reliability and consistency of the data. Both NRTL and UNIQUAC models adequately capture the experimental data.